The teaching pathologists association of Mumbai: A legacy that lives on - Jaya Deshpande; Rachana Binayke; Bhuvaneshwari Kandalkar; Manisha Khare (Indian Journal of Pathology and Microbiology)
The Teaching Pathologists Association of Mumbai was started by two doyens of pathology, Dr V. R. Khanolkar and Dr. P. V. Gharpure. They were the heads of the departments of pathology at Seth G S Medical College and Grant Government Medical college. The first meeting of the association was held in July 1935 at the Grant Medical College. The idea of the meetings was to know about the work done in other institutes and was attended by staff and students of these institutes. Soon Haffkine Institute joined, followed by Tata Memorial Hospital, TN Medical College, and Lokmanya Tilak Medical College in the late 1960s, with the latest entrant being HBT Medical College in 2023. The meetings that started in 1935 have continued till date (2023) with over 500 meetings being conducted so far. The nature of the meetings was in the form of a presentation by a postgraduate or faculty member. It was left to the discretion of the head of the department. This has been a unique association with no formal office bearers and runs purely on the understanding and cooperation of the senior teachers of these institutes. It has nurtured the spirit of mutual cooperation among the various medical institutes in Mumbai with the exchange and sharing of views and material. This article describes the beginning and subsequent growth of this association, the likes of which are yet to be seen elsewhere.